Evaluation of the Atherogenic Index of Plasma in the Prognostic Value of Ischemic Heart Failure Post-Percutaneous Coronary Intervention - Yinxiao Xu; Biyang Zhang; Meishi Ma; Yi Kan; Tienan Sun; Xin Huang; Yujie Zhou (Reviews in Cardiovascular Medicine)
Background: The atherogenic index of plasma (AIP) is calculated as the logarithm of the triglyceride (TG) to high-density lipoprotein cholesterol (HDL-C) ratio. While previous studies suggested that TG and HDL-C levels were linked to the prognosis in various cardiovascular conditions, including ischemic heart failure (IHF), there is limited research specifically examining AIP in the context of IHF. Therefore, our study sought to explore the association between AIP and the prognosis of IHF and to compare the predictive value of AIP, HDL-C, and TG levels for identifying patients with poor outcomes. Methods: This retrospective cohort study was conducted at a single institution involving 2036 IHF patients with post-percutaneous coronary intervention (PCI) who were followed for 36 months. Patients were divided into four groups categorized according to AIP quartiles. The primary outcome of interest was major adverse cardiovascular events (MACEs), while secondary outcomes included all-cause mortality, non-fatal myocardial infarction (MI), and any revascularization. Kaplan–Meier survival curves were used to evaluate the occurrence of endpoints across the four groups. Multivariate Cox regression analysis reinforced that AIP independently predicted primary and secondary outcomes. Restricted cubic spline (RCS) method was employed to examine the non-linear association between AIP and endpoints. Receiver operating characteristic (ROC) curves, combined with the Delong test, were used to assess and compare the predictive accuracy of AIP, TG, and HDL-C. Result: The incidence of MACEs (Q4:Q1 = 50.6:23.0, p < 0.001), all-cause death (Q4:Q1 = 25.0:11.6, p < 0.001), and any revascularization (Q4:Q1 = 21.6:9.6, p < 0.001) were significantly higher in patients with elevated AIP. The Kaplan– Meier curve analysis further supported a positive association between AIP and MACEs (plog-rank < 0.001). Multivariate Cox analysis showed that AIP was independently associated with the increased risk of MACEs (Q4:Q1 (HR (95% CI)): 2.84 (2.25–3.59), ptrend < 0.001), all-cause death (Q4:Q1 (HR (95% CI)): 2.76 (1.98–3.84), ptrend < 0.001), non-fatal MI (Q4:Q1 (HR (95% CI)): 3.01 (1.32–6.90), ptrend < 0.001), and any revascularization (Q4:Q1 (HR (95% CI)): 2.92 (2.04–4.19), ptrend < 0.001). In RCS, higher AIP was non-linearly relevant to an increased risk of MACEs (pnon-linear = 0.0112). In subgroup analysis, the predictive value of AIP for MACEs was more pronounced in the younger patient subgroup (pinteraction = 0.003). The ROC curves showed the predictive value of AIP (area under curve [AUC] = 0.641), HDL-C (AUC = 0.600), and TG (AUC = 0.629), and AIP had the best predictive value among TG (AIP:TG: difference in AUC (95% CI), 0.012 (0.001–0.024), p for Delong test = 0.028) and HDL-C (AIP:HDL-C: difference in AUC (95% CI), 0.041 (0.018–0.064), p for Delong test <0.001). Conclusion: In IHF patients after PCI, AIP was strongly relevant to an increased risk of MACEs and had the best predictive validity compared with TG and HDL-C.